2017
DOI: 10.1038/s41598-017-14482-x
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional regulation of acupuncture on extrahepatic biliary system: An approach in guinea pigs

Abstract: Clinically, acupuncture affects the motility of the extrahepatic biliary tract, but the underlining mechanisms are still unknown. We applied manual acupuncture (MA) and electrical acupuncture (EA) separately at acupoints Tianshu (ST25), Qimen (LR14), Yanglingquan (GB34), and Yidan (CO11) in forty guinea pigs (4 groups) with or without atropinization under anesthesia while Sphincter of Oddi (SO) myoelectric activities and gallbladder pressure were monitored. In both MA and EA groups, stimulation at ST25 or LR14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In the peripheral system, acupuncture can inhibit the contractions of Oddi's sphincter, bidirectionally regulate the gallbladder pressure, promote the secretion of hepatic bile and so on. [22][23][24][25] However, the central mechanism underlying acupuncture for BC relief still needs further investigation. Brain activity is closely correlated with the regulation of visceral function, and central integration is the key to achieving good regulation of visceral function by acupuncture.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the peripheral system, acupuncture can inhibit the contractions of Oddi's sphincter, bidirectionally regulate the gallbladder pressure, promote the secretion of hepatic bile and so on. [22][23][24][25] However, the central mechanism underlying acupuncture for BC relief still needs further investigation. Brain activity is closely correlated with the regulation of visceral function, and central integration is the key to achieving good regulation of visceral function by acupuncture.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In the peripheral system, acupuncture can inhibit the contractions of Oddi’s sphincter, bidirectionally regulate the gallbladder pressure, promote the secretion of hepatic bile and so on 22–25. However, the central mechanism underlying acupuncture for BC relief still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The common acupoints for treating cholelithiasis are the gallbladder, liver, and bladder meridians, such as Danshu (BL19), Riyue (GB24), and Qiuxu (GB40). However, studies indicating the benefit of acupuncture in discharging gallstones, attributed to its strengthening effect on the gallbladder contraction and bile secretion, are limited [25–27].…”
Section: Current Situation Of Tcm Use For Cholelithiasismentioning
confidence: 99%
“…e previous studies [21,22] of our research team showed that the gallbladder relaxed on a large scale after accepting acupuncture. e clinical trials and animal studies suggest that acupuncture on Yanglingquan (GB34), Qimen (LR14), and Yidan (CO11) is an effective method for regulating gallbladder motility [23,24]. Yet, the underlying mechanisms of acupuncture for gallstones remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%